Potential Activity Of Secondary Metabolites Of Kawista (Limonia Acidissima) As Neurodegenerative Diseases : A Network Pharmacology Approaches - Dina Siti Rahma M. Hentu; Muchlisin, M. Artabah; Jamil, Ahmad Shobrun; Astuti, Engrid Juni; Rafikayanti, Agustin (Sean Institute, 2024)
Kawista (Limonia acidissima) is a tropical plant traditionally used in South and Southeast Asian medicine, and its known for its rich nutritional profile and bioactive compounds. This study explores the therapeutic potential of kawista for neurodegenerative diseases. This study aims to investigate the potential of kawista in managing neurodegenerative through a pharmacological network approach. Proteins that can interact with secondary metabolites of kawista were predicted using SwissTargetPrediction, proteins related to neurodegenerative were obtained from GeneCards. The intersecting results were analyzed using STRING with GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment methods. From 47 secondary metabolites of kawista, 218 neuro-related proteins was identified potentially interacting with kawista's secondary metabolites. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and disease-gene association analyses highlighted key biological processes, molecular functions, cellular components, and pathways relevant to neurodegenerative disease mechanisms. The findings suggest that kawista's bioactive compounds could modulate critical pathways and receptor activities, offering insights into developing novel, effective therapies for neurodegenerative disorders. This research providing a scientific basis for kawista-based therapeutic strategies aimed at improving neurodegenerative disease outcomes.